Excess liquidity, bank pricing rules, and monetary policy - Agénor, Pierre-Richard; Aynaoui, Karim El (Journal of Banking & Finance, 2010)
This paper studies the implications of excess bank liquidity for the effectiveness of monetary policy in a simple model with credit market imperfections. The demand for excess reserves is determined by precautionary factors and the opportunity cost of holding cash. It is argued that excess liquidity may impart greater stickiness to the deposit rate in response to a monetary contraction and induce an easing of collateral requirements on borrowers – which in turn may translate into a lower risk premium and lower lending rates. As a result, asymmetric bank pricing behavior under excess liquidity may hamper the ability of a contractionary monetary policy to lower inflation.